1978
DOI: 10.1002/ijc.2910220302
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of circulating immune complexes in childhood acute lymphoblastic leukaemia

Abstract: Circulating immune complexes have been measured using the (125I)C1q binding test in 216 sera from 135 children with acute lymphoblastic leukaemia. Increased circulating immune complexes were detectable in 10.7% of the sera and 10.4% of the children. There was no correlation between the presence of circulating immune complexes and prognosis, but a strong correlation with a history of recent infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

1979
1979
1985
1985

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 5 publications
1
9
1
Order By: Relevance
“…This study, performed by Clq-BA and KgB-SP, confirms the previously reported increase of CIC in leukaemic sera Claque et al, 1978;Minden et al, 1980;Doan et al, 1980). The two methods were selected because of their different pattern of reactivity (Casali et al, 1977).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This study, performed by Clq-BA and KgB-SP, confirms the previously reported increase of CIC in leukaemic sera Claque et al, 1978;Minden et al, 1980;Doan et al, 1980). The two methods were selected because of their different pattern of reactivity (Casali et al, 1977).…”
Section: Discussionsupporting
confidence: 84%
“…A striking correlation between CIC and a low incidence of complete remission or even short survival was reported by Carpentier et a1 (1977) in acute leukaemia, using lZ5I-Clq binding assay (Clq-BA). Nevertheless, by the same method, other workers failed to confirm the prognostic value of CIC in acute pediatric leukaemia (Claque et al, 1978;Minden et al, 1980).…”
mentioning
confidence: 99%
“…Most patients who lacked detectable immune complexes entered remission, while the patients with detectable immune complexes did not. The specificity of the detected immune complexes can not be demonstrated with this technique and the significance of the results has been questioned (Claque et al, 1978) on the basis of a demonstrated strong correlation between presence of immune complexes and a history of recent infection and lack of correlation to the prognosis of the leukemic disease. In the present investigation no significant specific complement-dependent cytotoxicity against autochthonous leukemia cells could be detected in the untreated sera from seven patients with acute myelogenous leukemia harvested at the acute stage of the disease before initiation of any therapy.…”
Section: Discussionmentioning
confidence: 94%
“…Nevertheless, other authors [23] did not find a correlation between CIC levels obtained by the solid-phase bovine conglutinin test and clinical status in nonlymphatic leukemia. Clague et al [8], using the Ciq radioiodinated assay did not observe any correlation between the presence of CIC and the prognosis in ALL, although they observed a strong correlation with a history of recent infection.…”
Section: Discussionmentioning
confidence: 96%
“…There are several reports concerning the correlation of circulating immune complex (CIC) levels and the clinical status of malignant disease, including leukemia [1,5,8,15,17]. It has been suggested that immune complexes may inOffprint requests to : A. Segal-Eiras duce tumor progression changing the immune response of the host against malignant cells [2].…”
Section: Introductionmentioning
confidence: 99%